2021
DOI: 10.1093/cercor/bhab076
|View full text |Cite
|
Sign up to set email alerts
|

Myeloarchitectonic Asymmetries of Language Regions in the Human Brain

Abstract: One prominent theory in neuroscience and psychology assumes that cortical regions for language are left hemisphere lateralized in the human brain. In the current study, we used a novel technique, quantitative magnetic resonance imaging (qMRI), to examine interhemispheric asymmetries in language regions in terms of macromolecular tissue volume (MTV) and quantitative longitudinal relaxation time (T1) maps in the living human brain. These two measures are known to reflect cortical myeloarchitecture from the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…As one of the most prominent structural asymmetries across the entire human brain, PT structural asymmetries have been well recognized and widely believed to play a critical role in human auditory or language processing 8, 19,21,30,[43][44][45] . In concordance, anomalies of PT asymmetries in surface area or thickness have been reported in various brain disorders with auditory or language de cits, e.g., dyslexia, autism, and schizophrenia 17,21, 46-52 .…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most prominent structural asymmetries across the entire human brain, PT structural asymmetries have been well recognized and widely believed to play a critical role in human auditory or language processing 8, 19,21,30,[43][44][45] . In concordance, anomalies of PT asymmetries in surface area or thickness have been reported in various brain disorders with auditory or language de cits, e.g., dyslexia, autism, and schizophrenia 17,21, 46-52 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent developments in advanced imaging sequences, such as myelin water imaging (van der Weijden et al, 2020) or high-field laminar fMRI (Trampel et al, 2019), allow for an increasingly detailed study of cortical myelin contents. In this regard, our histology-validated depth profiles can be harnessed as ground-truth data to validate future in vivo imaging studies investigating myeloarchitecture (O’Muircheartaigh et al, 2019; Yuan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our digital atlas does not contain information on potential left-right asymmetries, since the original sources also do not contain any lateralization information. Nevertheless, a recent quantitative MRI study investigating myeloarchitectural metrics of the language system revealed heterogenous lateralization patterns (Yuan et al, 2021): While inferior frontal areas were left lateralized, the middle and superior temporal gyrus (Heschl’s gyrus and planum temporale) was found to be right lateralized. As such, future research should therefore be directed at potential functional implications of myeloarchitectural lateralization patterns in larger cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…While there are debates among the definitions, we defer to a broader (i.e., greater area) inclusionary definition. There are asymmetrical anatomical differences (i.e., hemispheric), one of the most notable is the planum temporale, in which we and others have discovered significant structural lateralized differences [31][32][33][34][35][36][37], which lead to significant functional differences in non-social domains [38][39][40]. For example, lesions of the lTPJ (left TPJ) typically lead to aphasias and verbal language disruption [41], visual-spatial neglect, however, is a common outcome of rTPJ damage [42,43].…”
Section: The Right Temporal Parietal Junctionmentioning
confidence: 91%